Restless legs syndrome is associated with increased risk of migraine - Maria Didriksen; Thomas F Hansen; Lise W Thørner; Kristoffer S Burgdorf; Christian Erikstrup; Ole B Pedersen; Helene M Paarup; Kaspar R Nielsen; Henrik Hjalgrim; Erik Sørensen; Henrik Ullum (SAGE Publishing, 2018)
Migraine and restless legs syndrome (RLS) are common disorders that are associated with a high level of individual suffering and major comorbidities. The aetiologies of the disorders are largely unknown, although both migraine and RLS have been linked to disturbances in the dopaminergic system and sleep issues, suggesting a relationship between the disorders. This study examines the association between RLS and migraine in a large population of otherwise healthy adults who are not taking medication. Cross-sectional study that included 20,938 participants enrolled in the Danish Blood Donor Study from 1 May 2015 to 1 February 2017. The study included complete information on migraines, the Cambridge-Hopkins RLS questionnaire, the Major Depression Inventory Scale, sex, age, body mass index (BMI), educational level, smoking status and alcohol consumption. Associations between RLS and migraine, with and without aura, were examined using multivariable logistic regression analysis. Among the participants, 4827 were self-reported migraine sufferers and 1091 were classified as suffering from RLS. Individuals with RLS had an increased risk of migraine compared to non-RLS sufferers, with an odds ratio (OR) = 1.52 (95% confidence interval: 1.33-1.73). For the investigated subtypes of migraine, this association was found to be OR = 1.55 (1.31-1.83) for migraines with aura and OR = 1.29 (1.09-1.52) for migraines without aura. We found a significantly increased occurrence of migraine in individuals with RLS. This risk was independent of sex, age, BMI, educational level, smoking status, alcohol consumption and depressive disorder. Our findings suggest that RLS and migraine may have a common aetiology.